Portfolio of Climate Resilient Options for Farming and Fishing Communities in Ivisan, Capiz - Méndez, Kharla Vianca S.; Vidallo, Rene R.; Rosimo, Magnolia M.; Servano, Gonzalo S.; Urdelas, Farah Gaud A.; Bernales, Lorna L.; Bernardo, Eisen Bernard; Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
The main purpose of this publication is to document climate smart agricultural options tested and implemented in Ivisan, Capiz, Philippines. The intention is to use evidence-based recommendations to promote out-scaling and upscaling. Participatory vulnerability assessment and action research helped in identification of climate resilient options. A community innovation fund supported the farmer-led action research. The investigators used a landscape approach in capturing how community-managed technologies worked in lowland, upland and coastal areas. This report presents the rationale of the technologies, details of the implementation process, actual farmers’ learnings and observed benefits. The compiled technological options resulted in a unique portfolio best-fitted to alleviate impacts of climate change while also addressing livelihood goals.